The ore mineralisations and postdiagenetic changes of sedimentary rocks in Donets basin - KURYLO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper deals with detailed description of conditions of ore-mineral complexes formation and postdiagenetic changes of sedimentary rocks in Donetsky basin.